Avaliação do impacto da expansão rápida da maxila sobre a permeabilidade nasal de crianças respiradoras orais com atresia maxilar decorrente ou não de rinite alérgica associada à asma - Carvalho, Paulo de Tarso Almeida [UNIFESP] (2019)
OBJECTIVES: The purpose of this intervention study was to evaluate the effects of rapid maxillary expansion (RME) on nasal permeability (PN) of mouth breathing children with maxillary atresia, whether or not associated with allergic rhinitis associated with asthma; as well as on the control of asthma in oral breathing children with associated asthma. MATERIAL AND METHOD: We selected 85 children (7 to 14 years old) with mixed or permanent dentures and were diagnosed as mouth breathing and had maxillary atresia with or without the presence of uni or bilateral crossbite. Of these 53 children completed the study. These patients were divided in three study groups according to the following characteristics: Group RAD (Allergic rhinitis, asthma, clinical treatment and disjunction) consisting of patients with allergic rhinitis and asthma who were submitted to RME (maxillary disjunction); Group RAC (allergic rhinitis, asthma and clinical treatment) consisting of patients with allergic rhinitis and asthma who were not submitted to RME, but were followed up with clinical treatment; Group D (mouth breathing and disjunction) formed by mouth breathing patients, without allergic rhinitis and without asthma, with maxillary atresia with or without crossbite (unilateral or bilateral) who suffered RME. Patients in the RAD and RAC groups were treated with nasal topical corticosteroid and / or systemic H1 antihistamine, both of continuous use, in addition to guidance on environmental exposure control. All patients were evaluated at the beginning, immediately before the device was disassembling (T1) and six months after the removal (T2) with: CARATkids score, acoustic rhinometry and computed tomography of the nasal cavity. The RAD and D patients suffered RME with an orthopedic device attached to their teeth (molars and upper premolars) called Hyrax, usually reached within 15 days of placement. RESULTS: Significant reduction in the CARATkids score occurred in the RAD group (-4.06, p <0.05), which was maintained by analyzing the asthma and rhinitis scores individually (-3.28 and -3.16, respectively). The evaluation of nasal volume by acoustic rhinometry (RA) showed an increase in all groups (RAC, RAD and D) (0.71, 0.99 and 0.69) evaluated. However, the increase in nasal volume in patients in the RAD group was significantly higher than that in RAC (0.99 x 0.71, respectively). Computed tomography of the nasal cavity showed the increase of volume in the three groups (RAC, RAD and D) (5.58, 3.61 and 5.68), with no differences between them. CONCLUSION: Rapid maxillary expansion in patients with allergic rhinitis and asthma and maxillary atresia associated with oral breathing results in increased nasal cavity volume and improvement of respiratory symptoms. However, it should not be used as a single treatment in the approach of patients with respiratory allergy.